Use of Scripture in 4QBeatitudes: A Torah-Adjustment to Proverbs 1–91 - Uusimäki, Elisa (Dead Sea discoveries, 2013)
This paper concerns the use of scripture in 4QBeatitudes (4Q525). The analysis of quotations and allusions shows that the status of Proverbs 1–9 as a source is primary, providing the model and salient motifs for the work. The use of Proverbs can, moreover, be associated with rewriting processes. Two features are distinctive: The author followed the order of the source to some extent in a manner reminiscent of rewriting. The motifs of female folly and her house were also used as a springboard in the creation of a poem (frg. 15). These observations suggest that 4Q525 reflects exegetical and interpretative methods attested in non-sapiential contexts. 4Q525 cannot be understood without recognizing its textual links to Proverbs, but other sources are similarly significant. The role of Psalms in particular can be described as ancillary and further directs the audience towards a Torah-centred approach to wisdom as well as implying a connection to the worship traditions of the Temple.